ChemInform Abstract: Ba2F2Fe1.5Se3: An Intergrowth Compound Containing Iron Selenide Layers. Issue 22 (12th May 2016) - Driss, Dalel; Janod, Etienne; Corraze, Benoit; Guillot‐Deudon, Catherine; Cario, Laurent
Abstract: The title compound is synthesized from stoichiometric mixtures of BaF2, Ba, Fe, and Se (675 °C, 72 h) and characterized by single crystal XRD and electrical resistivity and magnetic susceptibility measurements.